Tetraaryl pyrenes: photophysical properties, computational studies, crystal structures, and application in OLEDs. Issue 14 (15th October 2015) - El-Assaad, Tarek H.; Auer, Manuel; Castañeda, Raul; Hallal, Kassem M.; Jradi, Fadi M.; Mosca, Lorenzo; Khnayzer, Rony S.; Patra, Digambara; Timofeeva, Tatiana V.; Brédas, Jean-Luc; List-Kratochvil, Emil J. W.; Wex, Brigitte; et al.
Abstract : Nine 1, 3, 6, 8-tetraarylpyrenes were prepared and characterized for OLED-based blue-light emission. Abstract : Pyrene was derivatized in positions 1, 3, 6, and 8 to yield a series of nine tetraarylpyrenes for which absorption, emission, emission lifetimes and solvatochromism in solution were determined. The fluorescence quantum yields in thin films and crystalline state, electrochemistry, and quantum-chemical calculations were completed for the series along with the X-ray crystal structure analysis of compounds 1, 2, 4, 5, 7, and 9 . Compounds 2, 3, 4 as well as 7 were identified as the most suitable candidates for OLED application. Notably, in an unoptimized single-layer device geometry, these compounds exhibited blue electroluminescence coupled with impressively low turn-on voltages and high maximum luminances such as 2.8 V and 13 542 cd m −2 at 8.2 V for compound 2, respectively.